Flow and thermal study of MHD Casson fluid past a moving stretching porous wedge - Hussain, Majid; Ali, Akhtar; Ghaffar, Abdul; İnç, Mustafa (Springer, 2022)
This research provides the analysis of an analytical method named Homotopy analysis method which is applied to examine the series solutions/results on the thermal boundary layer flow over an extend-ing wedge. The wedge is considered to be absorptive with the existence of Ohmic heating and thermal radiation. The problem is non-dimensionalized by implementing similarity variables. Finally and more generally some figures are sketched to demonstrate the accuracy of the applied method and pertinent parameters such as MHD, Prandtl number, suction/injection C parameter, mixed convective parameter, Eckert E-c number and radiation parameter are presented. An attractive chance is attained when our achieved calculations are compared with already existing results in a limiting case; hence, dependable outcomes are being reflected.
Keywords: Fluid mechanics; Mixed convection; Ohmic heating; Radiation; Stretching wedge; Suction; injection